2012
DOI: 10.1016/j.rh.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Afasia y depresión post-ictus: una relación predictiva

Abstract: ResumenIntroducción/objetivos: La depresión se ha mostrado como la complicación psiquiátrica postictus más común, y la que se asocia con un pronóstico peor. Todavía existe incerteza en cuanto a su etiología y factores de riesgo. Algunos factores son reconocidos: gravedad del ictus, grado de discapacidad y déficit cognitivo. Por ello, es urgente definir nuevos factores que faciliten un diagnóstico temprano, lo cual puede disminuir los efectos negativos sobre el proceso de rehabilitación. Objetivos: Determinar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Within this percentage, less than 70% of patients return to work, and at least a quarter of them must adapt their condition to their work routine. 5,9,10,22,29 The majority of young adults who survive a stroke maintain a situation of independence (around 84-94%), however, in many cases psychosocial problems are described, such as mood changes, depression, divorce or unemployment. Post-stroke depression has an incidence of 38.7% among patients, this is due to the anxiety and stress caused by people not being able to carry out common activities independently physically.…”
Section: Discussionmentioning
confidence: 99%
“…Within this percentage, less than 70% of patients return to work, and at least a quarter of them must adapt their condition to their work routine. 5,9,10,22,29 The majority of young adults who survive a stroke maintain a situation of independence (around 84-94%), however, in many cases psychosocial problems are described, such as mood changes, depression, divorce or unemployment. Post-stroke depression has an incidence of 38.7% among patients, this is due to the anxiety and stress caused by people not being able to carry out common activities independently physically.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported an aphasia incidence of 31 per 100,000 person-years in patients with ischemic stroke [4]. Previous studies reporting the association between post-stroke aphasia (PSA) and subsequent depression came mainly from case-control studies [5][6][7][8][9][10][11][12][13][14] in hospital settings [5,7,12,13], with small sample sizes [5,[7][8][9][10]14] or shorter follow-up periods [5,8,14], or based on the inconsistent exclusion and inclusion criteria for identifying aphasia cases [15]. The risk of PSD in patients with PSA has not been compared between patients with ischemic stroke and hemorrhagic stroke [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…A presença de excesso de peso ou obesidade em associação com outros fatores de risco, como a hipertensão arterial, diabetes e ausência de atividade física geram grandes chances para o desenvolvimento do acometimento cerebral . Com a presença de um maior cuidado com a saúde e o aumento do conhecimento da população no cuidado com os fatores de risco considerados modificáveis com a adoção de hábitos alimentares saudáveis demonstra que os sujeitos, tem apresentado preocupação e tem sido um preditor para a redução dos acometimentos e das taxas de mortalidade entre os que apresentaram a doença (CARVALHO; PINTO, 2007;CAMOES-BARBOSA et al, 2012). …”
Section: Qsaviunclassified